Method for obtaining suitable charging rate of lithium-ion battery
By measuring the expansion thickness of lithium-ion batteries at different SOC stages, an appropriate charging ratio was calculated, which solved the problem of uneven expansion of the negative electrode caused by improper charging ratio, and improved the cycling performance and service life of the battery.
Patent Information
- Application Number
- CN202510027046.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-04
AI Technical Summary
During the charging process of lithium-ion batteries, if the charging rate is improper, it may lead to the expansion rate of the negative electrode too fast or uneven, causing the electrolyte to be unable to absorb and soak in time, resulting in local black spots or lithium-ion problems of the negative electrode, reducing the service life of the battery.
By charging three identical lithium-ion batteries, each battery is charged to three target SOCs (25~27%, 74~76% and 100%) and then disassembled. The expansion thickness of the negative electrode sheet is measured, and the appropriate charging ratio for each charging stage is calculated based on the relationship between the expansion thickness and the charging ratio.
By obtaining the better charging rate for each charging stage, ensuring uniform expansion of the negative electrode sheet during charging, avoiding the problem of the electrolyte not being able to infiltrate in time, extending the service life of the battery, and improving circulation performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery design, and in particular to a method for obtaining a suitable charging rate of a lithium-ion battery. Background Art
[0002] If an inappropriate charging rate is used during the charging process of a lithium-ion battery, the negative electrode may expand too quickly or unevenly, causing the electrolyte to not have enough time to be absorbed and infiltrated, thereby causing local black spots or lithium precipitation problems on the negative electrode, thereby reducing the battery's service life.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a method for obtaining a suitable charging rate of a lithium-ion battery, aiming to improve at least one of the problems mentioned in the background art.
[0005] The present invention is achieved in that: The present invention provides a method for obtaining a suitable charging rate of a lithium-ion battery, comprising: Three groups of identical batteries were charged at a test rate, and each group of batteries was disassembled after being charged to a target SOC, wherein the target SOCs were a first target SOC: 25-27% SOC, a second target SOC: 74-76% SOC, and a third target SOC: 100% SOC; After the batteries are disassembled, the expansion thickness of the negative electrode sheets of each group of batteries is measured to obtain the expansion thickness of the negative electrode sheets in the first charging stage, the second charging stage, and the third charging stage, respectively. The first charging stage is from 0% SOC to the first target SOC stage, the second charging stage is from the first target SOC to the second target SOC stage, and the third charging stage is from the second target SOC to the third target SOC stage; According to the formula X=a*u*ΔSOC / k, the charging rate of the target charging stage is calculated, where u is the target expansion rate of the negative electrode sheet, the u value of the first charging stage is 2.0~14μm / h, the u value of the second charging stage is 1.8~3.6μm / h, and the u value of the third charging stage is 1.8~11.7μm / h, k is the expansion thickness of the negative electrode sheet in each charging stage, and a is the correction coefficient 1C*h.
[0006] In an optional embodiment, the first target SOC is 25%, and the second target SOC is 75%.
[0007] In an optional embodiment, the test ratio is 0.15~0.3C.
[0008] In an optional embodiment, the test ratio is 0.2C.
[0009] In an optional embodiment, the expansion thickness of the negative electrode sheet in the first charging stage, the second charging stage, and the third charging stage are k1, k2, and k3, respectively; k1 is the thickness change of the negative electrode sheet of the battery charged to the first target SOC before and after charging. The thickness of the negative electrode sheet before charging is h0 and after charging is h1, k1=h1-h0; k2 is the thickness of the negative electrode sheet of the battery charged to the second target SOC minus h1, and the thickness of the group of negative electrode sheets after charging is h2, k2=h2-h1; k3 is the thickness of the negative electrode sheet of the battery charged to the third target SOC minus h2. The thickness of the group of negative electrode sheets after charging is h3, k3=h3-h2.
[0010] In an optional embodiment, the battery is a soft-pack laminate battery.
[0011] The present invention has the following beneficial effects: By studying the expansion of the battery during the charging process, the expansion thickness is linked to the charging rate in each charging stage, and the relationship between the two is obtained. Therefore, by charging at the test rate and testing the expansion thickness of the battery in each stage, the optimal charging rate for that stage can be obtained, and then a charging strategy that ensures uniform expansion of the negative electrode during the charging process is obtained, which improves the problem of local black spots or lithium precipitation at the negative electrode caused by the electrolyte not having enough time to infiltrate the negative electrode due to the excessively fast expansion rate of the negative electrode and poor expansion uniformity during the charging process of lithium-ion batteries, thereby improving the cycle performance and maximizing the performance of the battery cell. DETAILED DESCRIPTION
[0012] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0013] An embodiment of the present invention provides a method for obtaining a suitable charging rate of a lithium-ion battery, comprising: Three groups of identical batteries were charged at a test rate, and each group of batteries was disassembled after being charged to a target SOC, wherein the target SOCs were a first target SOC: 25-27% SOC, a second target SOC: 74-76% SOC, and a third target SOC: 100% SOC; After the batteries are disassembled, the expansion thickness of the negative electrode sheets of each battery group is measured to obtain the expansion thicknesses k1, k2, and k3 of the negative electrode sheets in the first charging stage, the second charging stage, and the third charging stage, respectively. The first charging stage is from 0% SOC to the first target SOC stage, the second charging stage is from the first target SOC to the second target SOC stage, and the third charging stage is from the second target SOC to the third target SOC stage; According to the formula X=a*u*ΔSOC / k, the charging rate of the target charging stage is calculated, where u is the target expansion rate of the negative electrode sheet, the u value of the first charging stage is 2.0~14μm / h, the u value of the second charging stage is 1.8~3.6μm / h, and the u value of the third charging stage is 1.8~11.7μm / h, k is the expansion thickness of the negative electrode sheet in each charging stage, in μm, and a is the correction coefficient 1C*h.
[0014] The method provided by the present invention studies the expansion thickness of the battery at each charging stage, relates the expansion thickness to the charging rate at each charging stage, and obtains a relationship between the two, so that the optimal charging rate at each stage can be obtained by testing the expansion thickness of the battery at each stage, and then a charging strategy for ensuring uniform expansion of the negative electrode sheet during the charging process is obtained, thereby improving the problem of local black spots or lithium precipitation at the negative electrode caused by the electrolyte not having enough time to infiltrate the negative electrode due to the excessively fast expansion rate and poor expansion uniformity during the charging process of the lithium-ion battery, thereby improving the cycle performance and maximizing the performance of the battery cell.
[0015] Optionally, the first target SOC is 25%, and the second target SOC is 75%.
[0016] Optionally, in order to avoid the influence of too large a magnification on the accuracy of the test result, the test magnification is 0.15-0.3C, preferably 0.2C.
[0017] Specifically, the expansion rates of the negative electrode sheet in the first charging stage, the second charging stage, and the third charging stage are k1, k2, and k3, respectively; k1 is the thickness change of the negative electrode sheet of the battery charged to the first target SOC before and after charging. The thickness of the negative electrode sheet before charging is h0 and after charging is h1, k1=h1-h0; k2 is the thickness of the negative electrode sheet of the battery charged to the second target SOC minus h1, and the thickness of the group of negative electrode sheets after charging is h2, k2=h2-h1; k3 is the thickness of the negative electrode sheet of the battery charged to the third target SOC minus h2. The thickness of the group of negative electrode sheets after charging is h3, k3=h3-h2.
[0018] Optionally, the battery is a soft-pack laminate battery.
[0019] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0020] Example 1 (1) Obtaining charging strategy Provide multiple test batteries, positive electrode sheet: the current collector is 13μm aluminum foil, the active layer is composed of lithium iron phosphate: conductive agent (SP): binder (PVDF): dispersant in a mass ratio of 96.9%:1.0%:1.8%:0.3%; negative electrode sheet: the current collector is 6μm copper foil, the active layer is composed of graphite: conductive agent (SP): thickener (CMC): binder (SBR) in a mass ratio of 95.0%:1.9%:1.3%:1.8%; the separator is PP film; the electrolyte formula is EC, EMC, DEC and PC, the volume ratio is 32:60:5:3, the lithium salt in the electrolyte is LiPF6, the concentration is 1mol / L, and the battery capacity is 50Ah.
[0021] The test batteries were divided into 4 groups, each with 12 batteries. All batteries were uniformly discharged to 2.5V at 0.2C. Three batteries discharged to 2.5V were directly taken from the first group without charging. The batteries in the second group were charged to 25% SOC at 0.2C. The batteries in the third group were charged to 75% SOC at 0.2C. The batteries in the fourth group were charged to 100% SOC at 0.1C.
[0022] After charging, all batteries were disassembled and the thickness of the negative electrode sheet of each battery was measured. The average thickness of the negative electrode sheet of each group of batteries was taken. The average thickness h0 of the first group of batteries was 132.93μm, the average thickness h1 of the second group of batteries after charging was 135.84μm, the average thickness h2 of the third group of batteries after charging was 136.75μm, and the average thickness h3 of the fourth group of batteries after charging was 140.40μm. It was calculated that k1 was 2.91μm, k2 was 0.91μm, and k3 was 3.65μm.
[0023] In the first charging stage, u is 14μm / h, in the second charging stage, u is 3.6μm / h, and in the third charging stage, u is 11.7μm / h. According to the formula X=a*u*ΔSOC / k, the charging rate in the first charging stage is 14*0.25 / 2.91=1.2C; the charging rate in the second charging stage is 3.6*0.5 / 0.91=1.98C, and the charging rate in the third charging stage is 11.7*0.25 / 3.65=0.8C.
[0024] Therefore, the charging strategy is: 0~25%SOC, 1.2C; 25~75%SOC, 1.98C; 75~100%SOC, 0.8C.
[0025] (2) Verify reliability Experimental Group: A new battery identical to that in step (1) was subjected to charge and discharge cycles, with the charging strategy being the charging strategy in step (1) and the discharging strategy being 1C. The battery was subjected to 1000 charge and discharge cycles, after which the battery was disassembled and the appearance of the negative electrode sheet was observed, and the statistics were recorded in Table 1. The statistical results showed that there was no obvious lithium deposition or black spots on the surface of the negative electrode sheet, indicating that the charging strategy obtained by the method provided in this embodiment is reliable.
[0026] Control group 1: The battery was charged at 0-25% SOC, 1.5 C; 25-75% SOC, 1.98 C; 75-100% SOC, 0.8 C, and discharged at 1 C for 1000 charge and discharge cycles. After that, the battery was disassembled and the appearance of the negative electrode sheet was observed, and the statistics were recorded in Table 1. From the results in Table 1, it can be seen that there is slight lithium deposition on the surface of the negative electrode sheet, indicating that the charging rate in the first charging stage is too large. It is difficult to obtain a good charging effect if the charging rate obtained in this embodiment is not used for charging.
[0027] Control group 2: The battery was charged at 0-25% SOC, 1.2C; discharged at 25-75% SOC, 2.3C; and 75-100% SOC, 0.8C, and discharged at 1C for 1000 charge and discharge cycles. The battery was then disassembled and the appearance of the negative electrode sheet was observed, and the statistics were recorded in Table 1. From the results in Table 1, it can be seen that there is severe lithium deposition on the surface of the negative electrode sheet, indicating that the charging rate in the second charging stage is too large. It is difficult to obtain a good charging effect if the charging rate obtained in this embodiment is not followed.
[0028] Control group 3: The battery was charged at 0-25% SOC, 1.2C; discharged at 25-75% SOC, 1.98C; and 75-100% SOC, 1.1C, and discharged at 1C for 1000 charge and discharge cycles. The battery was then disassembled and the appearance of the negative electrode sheet was observed, and the statistics were recorded in Table 1. From the results in Table 1, it can be seen that there is severe lithium deposition on the surface of the negative electrode sheet, indicating that the charging rate in the third charging stage is too large. It is difficult to obtain a good charging effect if the charging rate obtained in this embodiment is not followed.
[0029] Example 2 (1) Obtaining charging strategy Provide multiple test batteries, positive electrode sheet: the current collector is 13μm aluminum foil, the active layer is composed of lithium iron phosphate: conductive agent (SP): binder (PVDF): dispersant in a mass ratio of 96.4%:1.5%:1.9%:0.2%; negative electrode sheet: the current collector is 6μm copper foil, the active layer is composed of graphite: conductive agent (SP): thickener (CMC): binder (SBR) in a mass ratio of 95.3%:2.0%:1.0%:1.7%; the separator is PP film; the electrolyte formula is EC, EMC, DEC and PC, the volume ratio is 32:60:5:3, the lithium salt in the electrolyte is LiPF6, and the concentration is 1mol / L; the battery capacity is 50Ah.
[0030] The test batteries were divided into 4 groups, each with 12 batteries. All batteries were uniformly discharged to 2.5V at 0.2C. Three batteries were directly discharged to 2.5V in the first group without charging. The batteries in the second group were charged to 25% SOC at 0.2C. The batteries in the third group were charged to 75% SOC at 0.2C. The batteries in the fourth group were charged to 100% SOC at 0.2C.
[0031] After charging, all batteries were disassembled, and the thickness of the negative electrode sheet of each battery was measured. The average thickness of the negative electrode sheet of each group of batteries was taken. The average thickness h0 of the first group of batteries was 130.52μm, the average thickness h1 of the second group of batteries after charging was 133.20μm, the average thickness h2 of the third group of batteries after charging was 134.19μm, and the average thickness h3 of the fourth group of batteries after charging was 137.73μm. It was calculated that k1 was 2.68μm, k2 was 0.99μm, and k3 was 3.54μm.
[0032] In the first charging stage, u is 14μm / h, in the second charging stage, u is 3.6μm / h, and in the third charging stage, u is 11.7μm / h. According to the formula X=a*u*ΔSOC / k, the charging rate in the first charging stage is 14*0.25 / 2.68=1.31C; the charging rate in the second charging stage is 3.6*0.5 / 0.99=1.82C, and the charging rate in the third charging stage is 11.7*0.25 / 3.54=0.83C.
[0033] Therefore, the charging strategy is: 0~25%SOC, 1.31C; 25~75%SOC, 1.82C; 75~100%SOC, 0.83C.
[0034] (2) Verify reliability Experimental Group: A new battery identical to that in step (1) was subjected to charge and discharge cycles, with the charging strategy being the charging strategy in step (1) or , and the discharging strategy being 1C, and the charge and discharge cycles being 1000 cycles, after which the negative electrode sheet was disassembled and observed for apparent conditions, which are statistically reported in Table 1. From the results in Table 1, it can be seen that there is no obvious lithium deposition or black spots on the surface of the negative electrode sheet, indicating that the charging strategy obtained by the method provided in this embodiment is reliable.
[0035] Control group 1: The battery was charged at 0-25% SOC, 1.6C; 25-75% SOC, 1.82C; 75-100% SOC, 0.83C, and discharged at 1C for 1000 charge and discharge cycles. The battery was then disassembled and the appearance of the negative electrode sheet was observed, and the statistics were recorded in Table 1. From the results in Table 1, it can be seen that there is slight lithium deposition on the surface of the negative electrode sheet, indicating that the charging rate in the first charging stage is too large. It is difficult to obtain a good charging effect if the charging rate obtained in this embodiment is not followed.
[0036] Control group 2: The battery was charged at 0-25% SOC, 1.31C; discharged at 25-75% SOC, 2.2C; and 75-100% SOC, 0.83C, and cycled at 1C for 1000 times. The battery was then disassembled and the appearance of the negative electrode sheet was observed, and the statistics were recorded in Table 1. From the results in Table 1, it can be seen that there is severe lithium deposition on the surface of the negative electrode sheet, indicating that the charging rate in the second charging stage is too large. It is difficult to obtain a good charging effect if the charging rate obtained in this embodiment is not followed.
[0037] Control group 3: The battery was charged at 0-25% SOC, 1.31C; discharged at 25-75% SOC, 1.82C; and 75-100% SOC, 1.1C, and cycled at 1C for 1000 times. The battery was then disassembled and the appearance of the negative electrode sheet was observed, and the statistics were recorded in Table 1. From the results in Table 1, it can be seen that there is severe lithium deposition on the surface of the negative electrode sheet, indicating that the charging rate in the third charging stage is too large. It is difficult to obtain a good charging effect if the charging rate obtained in this embodiment is not followed.
[0038] Example 3 (1) Obtaining charging strategy Provide multiple test batteries, positive electrode sheet: the current collector is 13μm aluminum foil, the active layer is composed of lithium iron phosphate: conductive agent (SP): binder (PVDF): dispersant in a mass ratio of 96.4%:1.5%:1.9%:0.2%; negative electrode sheet: the current collector is 6μm copper foil, the active layer is composed of graphite: conductive agent (SP): thickener (CMC): binder (SBR) in a mass ratio of 95.5%:1.9%:0.8%:1.8%; the separator is PP film; the electrolyte formula is EC, EMC, DEC and PC, the volume ratio is 32:60:5:3, the lithium salt in the electrolyte is LiPF6, and the concentration is 1mol / L; the battery capacity is 50Ah.
[0039] The test batteries were divided into 4 groups, each with 12 batteries. All batteries were uniformly discharged to 2.5V at 0.2C. Three batteries discharged to 2.5V were directly taken from the first group without charging. The batteries in the second group were charged to 25% SOC at 0.2C. The batteries in the third group were charged to 75% SOC at 0.2C. The batteries in the fourth group were charged to 100% SOC at 0.2C.
[0040] After charging, all batteries were disassembled and the thickness of the negative electrode sheet of each battery was measured. The average thickness of the negative electrode sheet of each group of batteries was taken. The average thickness h0 of the first group of batteries was 131.28μm, the average thickness h1 of the second group of batteries after charging was 134.13μm, the average thickness h2 of the third group of batteries after charging was 135.23μm, and the average thickness h3 of the fourth group of batteries after charging was 138.92μm. It was calculated that k1 was 2.85μm, k2 was 1.10μm, and k3 was 3.69μm.
[0041] In the first charging stage, u is 14μm / h, in the second charging stage, u is 3.6μm / h, and in the third charging stage, u is 11.7μm / h. According to the formula X=a*u*ΔSOC / k, the charging rate in the first charging stage is 14*0.25 / 2.85=1.23C; the charging rate in the second charging stage is 3.6*0.5 / 1.1=1.64C, and the charging rate in the third charging stage is 11.7*0.25 / 3.69=0.79C.
[0042] Therefore, the charging strategy is: 0~25%SOC, 1.23C; 25~75%SOC, 1.64C; 75~100%SOC, 0.79C.
[0043] (2) Verify reliability Experimental Group: A new battery identical to that in step (1) was subjected to charge and discharge cycles, with the charging strategy being the charging strategy in step (1) or , and the discharging strategy being 1C, and the charge and discharge cycles being 1000, after which the battery was disassembled and the appearance of the negative electrode sheet was observed, and the statistics were recorded in Table 1. From the results in Table 1, it can be seen that there is no obvious lithium deposition and black spots on the surface of the negative electrode sheet, indicating that the charging strategy obtained by the method provided in this embodiment is reliable.
[0044] Control group 1: The battery was charged at 0-25% SOC, 1.6C; 25-75% SOC, 1.64C; 75-100% SOC, 0.79C, and discharged at 1C for 1000 charge and discharge cycles. After that, the negative electrode sheet was disassembled and observed. As shown in Table 1, there was slight lithium deposition on the surface of the negative electrode sheet, indicating that the charging rate in the first charging stage was too large. It is difficult to obtain a good charging effect if the charging rate obtained in this embodiment is not used for charging.
[0045] Control group 2: The battery was charged at 0-25% SOC, 1.23C; discharged at 25-75% SOC, 2.0C; and 75-100% SOC, 0.79C, and cycled at 1C for 1000 times. The battery was then disassembled and the appearance of the negative electrode sheet was observed, and the statistics were recorded in Table 1. From the results in Table 1, it can be seen that there is severe lithium deposition on the surface of the negative electrode sheet, indicating that the charging rate in the second charging stage is too large. It is difficult to obtain a good charging effect if the charging rate obtained in this embodiment is not followed.
[0046] Control group 3: The battery was charged at 0-25% SOC, 1.23 C; discharged at 25-75% SOC, 1.64 C; and 75-100% SOC, 1.1 C. The battery was discharged at 1 C for 1000 cycles. The battery was then disassembled and the appearance of the negative electrode sheet was observed. The results are summarized in Table 1. From the results in Table 1, it can be seen that there is slight lithium deposition on the surface of the negative electrode sheet, indicating that the charging rate in the third charging stage is too large. It is difficult to obtain a good charging effect if the charging rate obtained in this embodiment is not followed.
[0047] Table 1 The results of each embodiment after calculating the charge and discharge cycle for 1000 cycles
[0048] In Table 1, "0" indicates that there is basically no lithium deposition and no black spots, and "1" indicates that there is slight lithium deposition, the number of lithium deposition electrodes is 1-5, and the lithium deposition area is less than 4cm 2 "2" indicates severe lithium deposition, with 5-10 electrodes or 4-8 cm lithium deposition area. 2 , "3" indicates severe lithium deposition, with more than 10 electrodes or a lithium deposition area of 8 cm 2 above.
[0049] In the above three embodiments, the u value is taken as the upper limit of each charging stage. When u takes the upper limit, the charging strategy obtained can well avoid black spots on the surface of the negative electrode sheet. When u takes the lower limit, it can be determined without a doubt that there will be no lithium deposition black spots on the surface of the negative electrode sheet. When u takes the upper limit, the charging rate of each charging stage is the largest and the charging time is the shortest.
[0050] In summary, the method for obtaining a suitable charging rate for a lithium-ion battery provided by the present invention studies the expansion thickness of the battery during the charging process, relates the expansion thickness to the charging rate at each charging stage, and obtains a relationship between the two. Thus, by testing the expansion thickness of the battery at each stage, the optimal charging rate for that stage can be obtained, thereby obtaining a charging strategy that ensures uniform expansion of the negative electrode sheet during the charging process, thereby improving the problem of local lithium deposition or black spots on the negative electrode caused by the electrolyte not having time to infiltrate the negative electrode due to the excessively fast expansion rate and poor expansion uniformity during the charging process of the lithium-ion battery, thereby improving the cycle performance and maximizing the performance of the battery cell.
[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for obtaining a suitable charging rate of a lithium-ion battery, characterized in that: include: Three groups of identical batteries were charged at a test rate, and each group of batteries was disassembled after being charged to a target SOC, wherein the target SOCs were a first target SOC: 25-27% SOC, a second target SOC: 74-76% SOC, and a third target SOC: 100% SOC; After the batteries are disassembled, the expansion thickness of the negative electrode sheets of each battery group is measured to obtain the expansion thickness of the negative electrode sheets in the first charging stage, the second charging stage, and the third charging stage, respectively. The first charging stage is from 0% SOC to the first target SOC stage, the second charging stage is from the first target SOC to the second target SOC stage, and the third charging stage is from the second target SOC to the third target SOC stage; According to the formula X=a*u*ΔSOC / k, the charging rate X of the target charging stage is calculated, where u is the target expansion rate of the negative electrode sheet, the u value of the first charging stage is 2.0~14μm / h, the u value of the second charging stage is 1.8~3.6μm / h, and the u value of the third charging stage is 1.8~11.7μm / h, k is the expansion thickness of the negative electrode sheet in each charging stage, in μm, and a is the correction coefficient 1C*h.
2. The method according to claim 1, characterized in that The first target SOC is 25%, and the second target SOC is 75%.
3. The method according to claim 1, characterized in that: The test ratio is 0.15~0.3C.
4. The method according to claim 2, characterized in that: The test ratio is 0.2C.
5. The method according to claim 1, characterized in that The expansion thicknesses of the negative electrode sheet in the first charging stage, the second charging stage, and the third charging stage are k1, k2, and k3, respectively; k1 is the thickness change of the negative electrode sheet of the battery charged to the first target SOC before and after charging. The thickness of the negative electrode sheet before charging is h0 and after charging is h1, k1=h1-h0; k2 is the thickness of the negative electrode sheet of the battery charged to the second target SOC minus h1, and the thickness of the group of negative electrode sheets after charging is h2, k2=h2-h1; k3 is the thickness of the negative electrode sheet of the battery charged to the third target SOC minus h2. The thickness of the group of negative electrode sheets after charging is h3, k3=h3-h2.
6. The method according to claim 1, characterized in that The battery is a soft-pack laminate battery.